Hemipelvic pullout with pelvic visceral injuries. Hemipelvectomy - Torterolo, Edgardo; Farcic, Antonio; Fernández Perdomo, Gonzalo (Cirugía del Uruguay, 1976)
A man suffered an automobile accident and was thrown out of the car while the lower right limb remained caught. This resulted in the traumatic amputation of hemipelvis, right lower limb and penis. Urgency surgery consisted in completing amputation, hemostasis, and bladder and urethra reparation. Cutaneous closure was made by means of a rotated flap. A permanent colostomy was made in view of loss of sphincter and structures of posterior perineum. Evolution was good in spite of mutilations.